Pelatihan Jurnalistik di SMK Negeri 3 Raja Ampat Guna Mengenal Lebih Dekat Dunia Jurnalistik - Rahmat Makmur, Azharu; Syahrul; Abdillah, Fardan (LPPM IAIN Sorong, 2024)
SMK Negeri 3 Raja Ampat needs communication and information media between teachers, students, and parents in a school magazine. This results in journalism lessons needing to be taught to students. Based on these problems, it is necessary to hold journalism training for students of SMK Negeri 3 Raja Ampat. Journalism training benefits students as it helps them hone their creativity and talents. Based on these problems, the solution offered is to provide training. Theoretically, training participants are expected to be able to know how the process of making news starts from searching for data in the field, packaging, and compiling news until the news is worthy of being published or published. The method used is in the form of an explanation of journalism. To find out how well the participants understand the training provided, a pre-test and post-test are carried out first. The specific targets of this training include fostering students' interest and motivation in the importance of media to accommodate students' creativity and activities in channeling their talents and potential.